Pengaruh Digital Marketing, Social Media Engagement, dan Customer Trust Terhadap Loyalitas Pelanggan E-Commerce - Aris Kurniawan,; Lili Marlinah,; Yosie Noverha,; Vina Islami, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The development of e-commerce business is increasingly influenced by modern lifestyle with changes in international activities and industries. Factors in the development of e-commerce can be caused by the increasing number of entrepreneurs in recent years, the shift from traditional businesses to digital according to needs and increasingly broad competitors. This study uses quantitative research. This study aims to determine the effect of digital marketing, social media engagement, and customer trust on E-Commerce Customer Loyalty. This study focuses on E-Commerce users in Indonesia, by applying the Non-Probability Sampling technique to determine the sample obtained as many as 120 respondents. The results of this study have found that digital marketing, social media engagement, and customer trust have an effect on e-commerce customer loyalty.